Angelopoulos Sinemasında Mit'in yeniden yaratımı - Doğan, Alev (My University, 2019)
Bu çalışma, Dünya sinema tarihinin sayılı auteur yönetmenlerinden, özgün anlatım biçimi, kurgu konusuna yaklaşımları, tarihsel bakış açısı ile çağdaşlarından ayrılan Theodoros Anglepoulos’un sinemasında, mitlerin yeniden yorumlanışının incelemesini esas alarak hazırlanmıştır.Üç bölüme ayrılan bu tezin, ilk bölümünde mit kavramından yola çıkılarak, genel olarak mitoloji ve özelde Yunan Mitolojisi işlenmiş, ikinci bölümde Angelopoulos sinemasının tematik ve biçimsel özelliklerine yer verilmiş ve üçüncü yani son bölümde ise yönetmenin belli başlı filmleri ele alınarak, mitlerin nasıl yeniden işlendiği incelenmiştir.

This thesis work was contucted on the basis of re-interpretation of the mhyts in teh cinema of Theodoros Angelopoulos who is one of few auteur directors of the World cinema history. He is seperated from his contemporaries with his uniqe narrative style, distinctive approach of the fiction concept and his historical line of vision. This thesis consists of three main chapters. In the first chapter of this study, the term mythology was discussed from general mythology concept to the spesific Greek mythology in light of the myth Notion. In the second chapter, thematic and stylistic features of the Angelopoulos cinema were analyzed. Finally, in the last chapter, re-interpretation of the myths were examined by considering number of prominent movies of director.
Keywords: Auteur; Auteur Cinema; Greece; Mitoloji; Motion pictures; Mythology; Sinema; Thedoros Angelopoulos; Yunanistan